Análise da eficiência operacional em uma empresa da indústria metalomecânica que opera com pedidos assemble to order - Diefenthaler, Cristiano Erno (Universidade do Vale do Rio dos Sinos, 2020)
In the economic context in which organizations operate, the constant search to improve operational performance in order to remain competitive and profitable leads organizations to seek tools that help to monitor and analyze their performance, providing data, information and subsidies to the management team to make decisions and act for better performance. The concepts related to the Production System and the Operational Models: make-to-stock, assemble-to-order, make-to-order, engineering-to-order are discussed and evaluated within the context of Operational Efficiency and easy Productivity. An extensive research on the methods of measurement and analysis of efficiency found in the literature, proposes through a case study to analyze the efficiency of equipment in a manufacturing unit in the metalmechanical sector that operates with assemble-to-order orders. Through the efficiency analysis in the manufacturing macroprocesses, the process with the lowest performance was used for the application of three different methods of measurement and efficiency analysis and thus understand the behavior of the results found. In addition, the research showed that regardless of the method used to measure and analyze efficiency, the results verified are very similar, changing only the way of viewing the information, and for the decision making of the managers the correct and adequate data collection is more important than the method used to measure operational efficiency.
Keywords: Sistema de produção; Modelos operacionais; Eficiência operacional; Eficiência; Produtividade; Production system; Operational models; Operational efficiency; Efficiency; Productivity; ACCNPQ::Engenharias::Engenharia de Produção